Uncorrected Pelvic Obliquity Is Associated With Worse Health-related Quality of Life (HRQoL) in Children and Their Caregivers at the End of Surgical Treatment for Early Onset Scoliosis (EOS). Issue 4 (9th April 2022) - Matsumoto, Hiroko; Fano, Adam N.; Ball, Jacob; Roye, Benjamin D.; George, Ameeka; Garg, Sumeet; Erickson, Mark; Samdani, Amer; Skaggs, David; Roye, David P.; Vitale, Michael G.; ,
Abstract : Background: While largely of concern in nonambulatory patients, pelvic obliquity (PO) can be found in many patients with early onset scoliosis (EOS) and may remain following surgery. However, its association with health-related quality of life (HRQoL) in children and their caregivers at the end of treatment is not well understood. The purpose of this study was to investigate the association between residual PO and HRQoL in children and their caregivers at the end of surgical treatment in ambulatory patients with EOS. Methods: In this retrospective cohort study, a multicenter EOS registry was queried to identify ambulatory patients who underwent definitive posterior spinal fusion (PSF) from 2012 to 2019. Patients with fusions extending to the pelvis were excluded. PO was measured at least 1 year following PSF. HRQoL, Parental Burden, Financial Burden, and Satisfaction were assessed through the 24-Item Early Onset Scoliosis Questionnaire (EOSQ-24) also at a minimum of 1 year following PSF. Results: A total of 155 patients (12.5±2.1 y, 73.5% female) were included. Etiology distribution was 30.3% congenital, 12.9% neuromuscular, 21.3% syndromic, and 35.5% idiopathic. In congenital patients, those with residual PO >8 degrees had worse Satisfaction by 23.2 points compared with those with PO ≤8 degrees. In neuromuscular patients, those with residual PO >7 degrees had worse HRQoL by 16.1 points and Parental Burden by 22.3 points compared with their counterparts. In syndromic patients, those with residual PO >8 degrees had worse HRQoL by 14.8 points, Parental Burden by 16.4 points, and Satisfaction by 21.2 points compared with their counterparts. In idiopathic patients, those with >9 degrees of residual PO had worse HRQoL by 15.0 points and Financial Burden by 26.8 points compared with their counterparts. Conclusions: Remaining PO at the end of surgical treatment is associated with worse HRQoL in ambulatory children and their caregivers. These results suggest that correction of PO should remain a primary goal of treatment in patients with EOS undergoing surgery. Level of Evidence: Level II—multicenter retrospective cohort study investigating prognosis.